The dynamic magnetosphere - Liu, William; Fujimoto, Masaki (IAGA special sopron book series, 2011)
Despite the plethora of monographs published in recent years, few cover recent progress in magnetospheric physics in broad areas of research. While a topical focus is important to in-depth views at a problem, a broad overview of our field is also needed. The volume answers to the latter need. With the collection of articles written by leading scientists, the contributions contained in the book describe latest research results in solar wind-magnetosphere interaction, magnetospheric substorms, magnetosphere-ionosphere coupling, transport phenomena in the plasma sheet, wave and particle dynamics in the ring current and radiation belts, and extra-terrestrial magnetospheric systems. In addition to its breadth and timeliness, the book highlights innovative methods and techniques to study the geospace.